Numerical simulations of a CD nozzle and the influence of the duct length - Akhtar, Mohammad Nishat; Abu Bakar, Elmi; Aabid, Abdul; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
A numerical method is used to observe the effect of microjets control on wall pressure spreading in sudden expansion two-dimensional planar duct. In order to find the microjet effectiveness 2-jets of 1 mm diameter orifice located precisely at 900 of intervals along a pitch-circle-distance (PCD) of 1.3 times the exit diameter of the nozzle in the base were employed to control actively. At the present study, the Mach number was used to calibrate the entry to duct was 2.2, and the area ratio of 2.56. The focus in this study and investigate the influence of length-to-diameter ratio (L/D) of a suddenly expanded duct and its effect on the development of the flow field. Hence, to achieve this, the duct length has been varied from 2 to 10. Nozzles are producing such Mach numbers the experiments were performed operating at nozzle pressure ratio (NPR) 3, 5, 7, 9, and 11. The convergent-divergent nozzle geometry has been studied using the K-ε standard wall function turbulence model and independently check with the ANSYS software.